Understanding street culture: poverty, crime, youth and cool - Ilan, Jonathan (Palgrave Macmillan, 2015)
"An insightful and theoretically informed overview of street culture in various parts of the world - its origins, functions, manifestations and appeal - examining both its bearing on criminal lifestyles and on the cultivation of 'cool.' Contemporary examples and original research are used to evidence new ways of thinking about street culture today"--